2019
DOI: 10.1177/1079063219825872
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Inappropriate Sexual Behavior Among University Students: Using the Randomized Response Technique to Enhance Self-Reporting

Abstract: This article analyzes the efficacy of the randomized response technique (RRT) in achieving honest self-reporting about sexual behavior, compared with traditional survey techniques. A complex survey was conducted of 1,246 university students in Spain, who were asked sensitive quantitative questions about their sexual behavior, either via the RRT ( n = 754) or by direct questioning (DQ) ( n = 492). The RRT estimates of the number of times that the students were unable to restrain their inappropriate sexual behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Theoretical developments include much more complicated models (Abdelfatah, Mazloum, 2015;Batool, Shabbir, Hussain, 2017), optional randomised response techniques (Khalil, Zhang, Gupta, 2021) and scrambled randomised responses (Vishwakarma, Singh, 2021). Applications of RRTs include research on inappropriate sexual behaviour (Rueda, Cobo, López-Torrecillas, 2020), illegal waste disposal (Chong et al, 2019), ethics in business (Chu, So, Chung, 2018), corruption (Gingerich, 2010), and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical developments include much more complicated models (Abdelfatah, Mazloum, 2015;Batool, Shabbir, Hussain, 2017), optional randomised response techniques (Khalil, Zhang, Gupta, 2021) and scrambled randomised responses (Vishwakarma, Singh, 2021). Applications of RRTs include research on inappropriate sexual behaviour (Rueda, Cobo, López-Torrecillas, 2020), illegal waste disposal (Chong et al, 2019), ethics in business (Chu, So, Chung, 2018), corruption (Gingerich, 2010), and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical developments include much more complicated models (Abdelfatah, Mazloum, 2015;Batool, Shabbir, Hussain, 2017), optional randomised response techniques (Khalil, Zhang, Gupta, 2021) and scrambled randomised responses (Vishwakarma, Singh, 2021). Applications of RRTs include research on inappropriate sexual behaviour (Rueda, Cobo, López-Torrecillas, 2020), illegal waste disposal (Chong et al, 2019), ethics in business (Chu, So, Chung, 2018), corruption (Gingerich, 2010), and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Contextually, many studies have assessed the validity of RR methods, showing that they can produce more reliable answers than conventional data collection methods (eg, direct questioning (DQ) in face‐to face interviews, SAQs with paper and pencil and CASIs). The RRT has been applied in surveys covering a variety of sensitive topics, as drug use, racism, abortion, sexual victimization, cheating, and so on, as indicated in the articles of Perri et al and Rueda et al We found some more recent studies related with people's sexual practice in the United States, health care study of the dependence structure, inappropriate sexual behavior among university students, contaminants in the air and water, genital cutting in Southern Ethiopia, female sex workers in Taiyuan, China,, drug use in Republic of Georgia, illegal cable TV subscribers, and the right to receive welfare …”
Section: Introductionmentioning
confidence: 99%